ANALYSIS ON THE POTENTIAL OF KERTA SEMAYA SAMINAYA TO ENTER THE GERMAN MARKET - Bagus Dwija Bhaskara, Ida
Kerta Semaya Saminaya (KSS) is a sustainable Indonesian cocoa bean supplier. They produce organic fine or flavor cocoa beans that allows their product to become a premium. The problem however is that they are lacking buyers and wishes to expand their sales by exporting to a German buyer. As Germany would be able to appreciate their product as a premium and value it as such. Germany is also one of the biggest consumers of chocolate and importers of cocoa beans in the world. This brings forth the question of if it is possible for KSS to enter Germany. To understand this several aspects must be analyzed. We approach this by first looking into the buyer which is Germany. So first is to understand the conditions of the German market, its segments, and its characteristics. Then we need to link the capability of KSS to the German requirements. To analyze and research this both qualitative and quantitative research methodology is used in this research to gain information and identify alternatives for improvement of actions. However, the research will emphasize more on the qualitative data. Secondary data is used to provide general knowledge while primary data for a more detail understanding. The primary data gathered is from interviewing German buyers, Indonesian supplier, survey German market segment and spreading questionnaires. For analysis technique, descriptive analysis is performed. To penetrate the German market, the only available option is to go through the niche market. To even sell to the German market a variety of requirements are needed ranging from basic to the niche requirements. One important requirement in Germany is sustainability which is also the aim of KSS. Kerta Semaya Saminaya has the capability to sell and compete in the German market however they still require certain certifications and conformity to be able to enter the market which could be overcome by selling through a wholesaler.